Operation Planning Reservoir with Linear Programming Optimization Model for Water Demand of the Community In Aceh Besar District - Wesli Wesli (Indonesian Journal of Geography, 2015)
On the condition before building a dam, Aceh Besar district often a shortage of water for the needs of the community, so that people difficulty in doing their activities. There is a river in the Aceh Besar district named “Keuliling River”. The river is one of the watershed sub-basins of Krueng Aceh which has large enough potential of water to increase the supply of raw water in order to meet the water needs of the Banda Aceh City and Aceh Besar district.Therefore, a reservoir building was built that able to acomodate a large capacity of water. The resorvoir was named “Keuliling Reservoir”. “Reservoir Keuliling” has 38.20 km2 watershed areas, 259.94 hectares wide puddle on Normal Water Front (MAN), a total of 18,359,078 m3 bin normal water level at an elevation of 45.80 m and has an effective pitcher of 12.99,208 m3. The reservoir also serves as a provider of raw water for the development of inland fisheries, livestock, rice fields and others. The greatest needs are to be served by the reservoir is water requirement for paddy planting season Rendeng in October to December and the gadu growing season from April to June. To meet all these requirements then performed the planning operation of reservoir. Ie, by optimizing the volume of water storage at the end of the month through the optimization of the use of inflow data and outflow data. The optimization performed with optimization models Linear Programming. The results of the optimization is the volume of water in reservoirs that have large water needs, which in October is 13,380,986 m3, in November is 76,640,036 m3 and in December is 38,104,116 m3. Where in each month of the above conditions are still effective volume reservoirs at 12,992,080 m3. The results showed that from month to month never happened reservoir conditions at the level of the dead reservoirs, this illustrates that Keuliling reservoir can meet the water needs of the community.